Modular domains of the Dicistroviridae intergenic internal ribosome entry site - Jang, Christopher J. (Cold Spring Harbor Laboratory Press, 2010)
The intergenic region internal ribosome entry site (IGR IRES) of the Dicistroviridae viral family can directly assemble 80S ribosomes and initiate translation at a non-AUG codon from the ribosomal A-site. These functions are directed by two independently folded domains of the IGR IRES. One domain, composed of overlapping pseudoknots II and III (PKII/III), mediates ribosome recruitment. The second domain, composed of PKI, mimics a tRNA anticodon–codon interaction to position the ribosome at the ribosomal A-site. Although adopting a common secondary structure, the dicistrovirus IGR IRESs can be grouped into two classes based on distinct features within each domain. In this study, we report on the modularity of the IGR IRESs and show that the ribosome-binding domain and the tRNA anticodon mimicry domain are functionally interchangeable between the Type I and the Type II IGR IRESs. Using structural probing, ribosome-binding assays, and ribosome positioning analysis by toeprinting assays, we show that the chimeric IRESs fold properly, assemble 80S ribosomes, and can mediate IRES translation in rabbit reticulocyte lysates. We also demonstrate that the chimeric IRESs can stimulate the ribosome-dependent GTPase activity of eEF2, which suggests that the ribosome is primed for a step downstream from IRES binding. Overall, the results demonstrate that the dicistrovirus IGR IRESs are composed of two modular domains that work in concert to manipulate the ribosome and direct translation initiation.